Shrub-mediated effects on soil nitrogen determines shrub-herbaceous interactions in drylands of the Tibetan Plateau - Cui, Guangshuai; Pugnaire, Francisco I.; Yang, Liu; Zhao, Wanglin; Ale, Rita; Shen, Wei; Luo, Tianxiang; Liang, Eryuan; Zhang, Lin (Frontiers in Plant Science, 2023)
Introduction Shrub promotes the survival, growth and reproduction of understory species by buffering the environmental extremes and improving limited resources (i.e., facilitation effect) in arid and semiarid regions. However, the importance of soil water and nutrient availability on shrub facilitation, and its trend along a drought gradient have been relatively less addressed in water-limited systems. Methods We investigated species richness, plant size, soil total nitrogen and dominant grass leaf δ13C within and outside the dominant leguminous cushion-like shrub Caragana versicolor along a water deficit gradient in drylands of Tibetan Plateau. Results We found that C. versicolor increased grass species richness but had a negative effect on annual and perennial forbs. Along the water deficit gradient, plant interaction assessed by species richness (RIIspecies) showed a unimodal pattern with shift from increase to decrease, while plant interaction assessed by plant size (RIIsize) did not vary significantly. The effect of C. versicolor on soil nitrogen, rather than water availability, determined its overall effect on understory species richness. Neither the effect of C. versicolor on soil nitrogen nor water availability affected plant size. Discussion Our study suggests that the drying tendency in association with the recent warming trends observed in drylands of Tibetan Plateau, will likely hinder the facilitation effect of nurse leguminous shrub on understories if moisture availability crosses a critical minimum threshold.